The Role of OCB as a Mediator in Improving Employees Performance - Ana Kadarningsih; Vicky Oktavia; Amjad Ali (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2020)
Employee performance is a measure of the quality of human resources in a company, because employee performance is one important factor for the achievement of a company's goals. Employee performance can be influenced by several factors, such as training, work environment and organizational citizenship behavior (OCB). The purpose of this research is to determine the influence of training and work environment to employee’s performance with Organizational Citizenship Behavior (OCB) as the intervening. This research was conducted at the Semarang City Education Department by taking a sample of 115 respondents registered as active officials of the Semarang City Education Department. Data collection method is done through a questionnaire. Data analysis uses path analysis. The results of the study concluded that there is an influence of training and work environment on OCB, the influence of OCB on employee performance and OCB is able to mediate the relationship between training and work environment on employee performance.